Peningkatan Kesadaran Hukum dan Keterampilan Masyarakat dalam Pengelolaan Sampah Organik melalui Penyuluhan Hukum di Kelurahan Tohudan, Kecamatan Colomadu, Kabupaten Karanganyar - Lusia Indrastuti; Sinta Ana Pramita; Angela Tanujaya (Lembaga Pengembangan Kinerja Dosen, 2026)
The issue of household waste remains a major challenge in environmental management, influenced by the low public awareness in sorting and processing waste from its source. This condition results in an increase in the volume of waste disposed of at final processing sites and causes various environmental problems. This community service activity aims to increase legal awareness and community skills in organic waste management thru legal counseling and participatory-based training. The activity was conducted in Tohudan Village, Colomadu District, Karanganyar Regency using a participatory approach that actively involved the community thru counseling, interactive discussions, demonstrations, and hands-on practice. The materials presented included legal provisions regarding waste management, classification of types of waste, the importance of waste segregation at the source, various methods of processing organic waste, and the application of the Reduce, Reuse, and Recycle (3R) principle. The results of the activities showed an increase in public understanding of rights and obligations in waste management, an improvement in participants' ability to sort organic and inorganic waste, and an increase in knowledge about utilizing organic waste into compost and valuable products. The high participation of participants during the activities also indicates that an approach integrating legal education with practical training can encourage a change in community behavior toward more responsible waste management. Therefore, this community service activity contributes positively to building a culture of legal awareness, increasing community participation, and supporting sustainable household waste management as part of efforts to create a clean, healthy, and sustainable environment.